Modelo de distribución potencial de Leucaena leucocephala y Acacia farnesiana para el Noreste de México - López-Cantú, David Gilberto; Maldonado-Torres , Aracely; Crespo-Reyes, Elizabeth; Requena-Lara, Glenda Nelly; Morales Pacheco, Juan Francisco; Garay Martínez, Jonathan Raúl (Ecosistemas y Recursos Agropecuarios, 2025)
Models of potential distribution of species are a tool that allows the management, use and control of biodiversity. The objective of this research was to model the potential distribution of Leucaena leucocephala and Acacia farnesiana for Northeast Mexico (Nuevo León and Tamaulipas). A total of 19 bioclimatic variables were used to construct the models, which were obtained from the WorldClim database. A total of 143 records of A. farnesiana and 82 records of L. leucocephala were used. The ecological niche models were developed with the maximum entropy algorithm of the Maxent software, the value of the area under the curve was used, using the Tool for Partial-ROC program and the Jackknife method was used to estimate the relative contribution of each climate variable. The models showed a probability of suitability from 31 to 95% for A. farnesiana and from 30 to 92% for L. leucocephala. A larger area of suitability was observed for A. farnesiana in Tamaulipas, while for L. leucocephala, the area of suitability was smaller throughout the Northeast. The analysis of the area under the curve showed results of 0.869 for L. leucocephala and 0.787 for A. farnesiana, which is considered a statistically reliable performance of the model. In northeastern Mexico, it could be feasible to use L. leucocephala and A. farnesiana in extensive livestock systems, which would reduce the negative impacts of this productive activity on the environment and livestock agroecosystems.
Keywords: Clima árido; clima semiárido; leguminosa forrajera; variables bioclimáticas